2017
DOI: 10.1186/s12884-017-1456-8
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors and pregnancy outcomes associated with prepregnancy obesity: effect modification of parity in the nationwide Epifane birth-cohort

Abstract: BackgroundIn light of the adverse outcomes for mothers and offspring related to maternal obesity, identification of subgroups of women at risk of prepregnancy obesity and its related-adverse issues is crucial for optimizing antenatal care. We aimed to identify sociodemographic factors and maternal and neonatal outcomes associated with prepregnancy obesity, and we tested the effect modification of parity on these associations.MethodsIn 2012, 3368 mothers who had delivered in 136 randomly selected maternity ward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 49 publications
2
28
1
11
Order By: Relevance
“…For each case, we recorded the following data: (1) demographics, (2) type of placenta, (3) gestational history, (4) weight, height, and BMI, (5) indication of CS, (6) postpartum hemorrhage, blood loss, and the amount of transfused blood units, (7) NICU and hospital stays, (8) injuries, (9) congenital anomalies, and (10) maternal and neonatal complications. Data were entered in a self-structured proforma and were later transferred to SPSS for analysis.…”
Section: Source Of Data and The Study Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…For each case, we recorded the following data: (1) demographics, (2) type of placenta, (3) gestational history, (4) weight, height, and BMI, (5) indication of CS, (6) postpartum hemorrhage, blood loss, and the amount of transfused blood units, (7) NICU and hospital stays, (8) injuries, (9) congenital anomalies, and (10) maternal and neonatal complications. Data were entered in a self-structured proforma and were later transferred to SPSS for analysis.…”
Section: Source Of Data and The Study Variablesmentioning
confidence: 99%
“…It was reported that excess gestational weight gain, gestational diabetes, hypertensive complications, cesarean delivery, and increased infant weight were independently associated with pre-pregnancy obesity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Paritateak jaiotzako GParekin lotura adierazi du erregresio logistikoan. Ama multiparoen artean haurdunaldi aurreko obesitatea dutenek 1,7 aldiz arrisku handiagoa daukate adin gestazionalerako ume handiak izateko, ama nuliparoekin konparatuta (16).…”
Section: Eztabaidaunclassified
“…30.0 kg/m2, is increasing over time. 5,12,18 Pregestational BMI is a risk factor for the development of maternal and perinatal complications. 24,27 In the clinical practice, obesity and gestational diabetes commonly coexist and it is controversial which one the two conditions (gestational diabetes or maternal obesity) is more strongly associated with risk for adverse maternal and neonatal outcomes.…”
Section: Introductionmentioning
confidence: 99%